Schule und Unterricht im digitalen Wandel Ansätze und Erträge rekonstruktiver Forschung - Proske, Matthias; Rabenstein, Kerstin; Moldenhauer, Anna; Thiersch, Sven; Bock, Annekathrin; Herrle, Matthias; Hoffmann, Markus; Langer, Anja; Macgilchrist, Felicitas; Wagener-Böck, Nadine; Wolf, Eike (Verlag Julius Klinkhardt, 2023)
The volume "Schule und Unterricht im digitalen Wandel" (School and Teaching in the Digital Transformation) explores perspectives of reconstructive-sensual research for the study of school and teaching in the digital transformation. Four empirical studies are presented and their findings are classified theoretically and methodologically. The studies are interested in the changes as well as the stability of practices in the classroom when digital media are used. And they investigate how students and teachers interpret the transformation processes that accompany digitization. The research perspectives generated are contoured in greater depth by the discussion of the studies' findings with regard to central questions of digital transformation and its research at the end of the volume.